6th International Symposium on High-Temperature Metallurgical Processing - Jiang, Tao; Hwang, Jiann-Yang; Alvear, Gerardo; Yucel, Onuralp; Mao, Xinping; Yong Sohn, Hong; Ma, Naiyang; Mackey, Phillip; Battle, Thomas (The Minerals, Metals & Materials Series,, 2016)
The analysis, development, and/or operation of high temperature processes that involve the production of ferrous and nonferrous metals, alloys, and refractory and ceramic materials are covered in the book. The innovative methods for achieving impurity segregation and removal, by-product recovery, waste minimization, and/or energy efficiency are also involved. Eight themes are presented: 1: High Efficiency New Metallurgical Process and Technology 2: Fundamental Research of Metallurgical Process 3: Alloys and Materials Preparation 4: Direct Reduction and Smelting Reduction 5: Coking, New Energy and Environment 6: Utilization of Solid Slag/Wastes and Complex Ores 7: Characterization of High Temperature Metallurgical Process.